2011
DOI: 10.1590/s1516-80342011000100008
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade dos potenciais evocados auditivos em indivíduos adultos com audição normal

Abstract: OBJETIVO: Avaliar a estabilidade dos parâmetros dos potenciais evocados auditivos em adultos normais. MÉTODOS: Foram submetidos à avaliação audiológica e eletrofisiológica (potencial evocado auditivo de tronco encefálico - PEATE, potencial evocado auditivo de média latência - PEAML e potencial cognitivo - P300) 49 indivíduos normais, de 18 a 40 anos (25 do gênero feminino e 24 do gênero masculino). Realizou-se reavaliação três meses após a avaliação. RESULTADOS: Foram observadas diferenças entre os gêneros na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 17 publications
(20 reference statements)
1
24
2
7
Order By: Relevance
“…For P3 potential there was no difference between the ears (Figure 2), considering latency and amplitude, which corroborates with current study 19 which was carried out with binaural stimulation and analyzed values only one ear, for possible absence of difference between them 20,21 . Other studies also showed no difference between right and left ears in the latency of P3 potential, and amplitude was not considered, corroborating the findings of this, as other authors 22 consider the latency and amplitude of P3 potential it was not found any statistically significant differences.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For P3 potential there was no difference between the ears (Figure 2), considering latency and amplitude, which corroborates with current study 19 which was carried out with binaural stimulation and analyzed values only one ear, for possible absence of difference between them 20,21 . Other studies also showed no difference between right and left ears in the latency of P3 potential, and amplitude was not considered, corroborating the findings of this, as other authors 22 consider the latency and amplitude of P3 potential it was not found any statistically significant differences.…”
Section: Discussionsupporting
confidence: 89%
“…Our study corroborates the aforementioned study, as there was no significant difference for the finding as to latency. In the literature there was also the rare stimulus counting in two ways namely: counting mentally 27 , counting mentally and raising the hand 21,26,28 to hear it and after, count aloud 21,29 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the diagnosis suggests a possible alteration in the auditory system up to the level of the brainstem. The BAEP can give electrophysiological evidence on the auditory processing of linguistic information (10) . As such, the alteration observed with the BAEP in the second case, associated with normal auditory thresholds, suggests that speech discrimination in the presence of noise may be impaired.…”
Section: Discussionmentioning
confidence: 99%
“…previas al examen ningún medicamento que pueda generar algún tipo de estimulación, o estimulantes como cafeína, té, chocolate, cigarrillo u otros que puedan afectar el sistema nervioso central (de Miranda et al, 2012). Igualmente, como criterio de exclusión, estudios consideraron la presencia de pérdida auditiva, los trastornos de procesamiento auditivo, trastornos o déficit del lenguaje y/o cualquier compromiso clínico o cognitivo que impidiese o dificultase la realización de los exámenes, además, como primer paso, los sujetos deben ser evaluados usando la otoscopía, impendaciometría y potenciales evocados auditivos de tronco encefálico, con el fin de conocer el estado de la vía auditiva (Massa et al, 2011;Matas et al, 2011;Muñoz-Avilés et al;Didoné et al).…”
Section: Introductionunclassified